Respiratory syncytial virus infection in children less than five years of age presenting as severe community-acquired pneumonia - Suganya, Mahalingam; Kalpana, Sivasambo; S, Elilarasi; B, Sarathbalaji (Indian Journal of Child Health, 2018)
Background: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infection in young children in both the community and hospital setting. Ongoing surveillance of the clinical and molecular epidemiology of RSV genotypes is important to characterize prevalent and emerging genotypes that may have impact on vaccine development. Objective: To assess the epidemiology of RSV infection in children <5 years of age in a tertiary care hospital. Materials and Methods: Children <5 years of age hospitalized with severe community-acquired pneumonia (CAP) were included in the study. Nasopharyngeal aspirate was taken for RSV reverse-transcriptase polymerase chain reaction. Results: A total of 100 children were recruited in the study. clinicoepidemiological epidemiological and radiological features were analyzed. The prevalence of RSV infection in children <60 months of age admitted with the features of severe pneumonia in our study was 30% with almost equal proportion of RSV A and B groups. Underlying congenital heart disease and family history of asthma were identified as significant risk factors. There were no significant clinical and radiological features to distinguish RSV from non-RSV disease. Conclusions: This study highlights the relevance of RSV infection in hospitalized cases of CAP in our region. Our findings warrant the conduct of further investigations which can help design strategies for controlling the disease. If RT-PCR could be used in children with severe pneumonia who are hospitalized, an accurate diagnosis of RSV bronchiolitis can be made in high percentage of children.